Pertumbuhan Bibit Kakao (Theobroma cacao L.) pada Berbagai Jenis Klon dan Jenis Pupuk Kandang - Widyastuti, Leni Sri; Parapasan, Yonathan; Same, Made (Politeknik Negeri Lampung, 2021)
Several factors affect the production of cocoa (Theobroma cacao L.), one of which is the quality of seedlings. The quality of seedlings is affected by the type of clones and the composition of the planting media. This study aims to obtain the influence of clone types and types of manure and the interaction between clone types and types of manure on the growth of cocoa seedlings. The study was conducted in the teaching farm and the laboratory of the Politeknik Negeri Lampung from January 2017 to June 2017. The method used was a Randomized Block Design (RBD) factorial pattern consisting of two factors. The first factor is the type of clone consisting of three levels, namely K1 = TSH clone 858, K2 = ICS 60, and K3 = TSH 908. The second factor consisting of four levels namely P0 = control, P1 = chicken manure, P2 = cow manure, and P3 = goat manure. The results showed that the use of TSH 858, ICS 60, and TSH 908 clones had the same effect on all observed variables. However, the use of manure has a significant effect on each variable, but the amount of leaf chlorophyll is relatively the same between clone types and types of manure. There are interactions between clone types and types of manure.